Investigation of non volatile resistive switching behaviour using rose petal. (2022) - Yasmin Rahman, Farhana; Sarkar, Surajit; Banik, Hritinava; Jashim Uddin, Md.; Bhattacharjee, Debajyoti; Arshad Hussain, Syed
Abstract: Natural materials based electronic devices have the potential to transform the scope and accessibility of electronics by offering incredibly inexpensive bio degradable and variety of components. In this paper, we report architecture for a (Write Once Read Many) WORM, based on rose petals. The Au/Rose/ITO device demonstrates non volatile resistive switching with WORM memory behavior. The WORM memory performance was found to be excellent having memory window (1.23 × 10 2 ), data retention (7200) sec, read endurance 10 cycle and device stability (greater than7)days. Analysis of results revealed that the charge trapping process with the increase of the bias is responsible for the switching behavior. As a whole, rose based WORM device displays an important milestone towards the realization of non volatile memory applications.